The effect of positive orientation and perceived social support on foreign language classroom anxiety. (June 2018) - Jin, Yin Xing; Dewaele, Jean-Marc
Abstract: The present study reports on the effect of learners' positive orientation, perceived teacher and student emotional support on their foreign language classroom anxiety. One hundred and forty-four Chinese L1 second-year university-level participants filled out the Positivity Scale, the Foreign Language Classroom Anxiety Scale, and the Teacher/Student Emotional Support Scale. Hierarchical regression analyses revealed that positive orientation was a significant negative predictor of FL anxiety. The relationship between perceived student support and anxiety ceased to be significant as positive orientation entered the model. Perceived teacher support did not significantly predict FL classroom anxiety at each step of the analysis. The results are discussed in line with previous findings as well as their practical implications for foreign language teaching and learning in Chinese universities.